Palavra e imagem : paisagens disparadas em Armando Freitas Filho - Rodrigues, Cristiane Lemos (2006)
The purpose of this work is to critically reflect upon the relationship between the brazilian poetical speech and the several values activated by the image in contemporaneity, so to problemize the question of representation. To do so, we have chosen as the object of study the work of the carioca writer Armando Freitas Filho, which, started with the publication of his first book, Word, in 1963, and is still productive until today. The way through which the relationships are built between the subjectivity and the poetical views leads us towards a tense and productive dialogue with the hegemonic forms of visibility in the contemporary culture. In this way, we identify in the armandiana poetics a critical look over a western ocularcentric tradition, originated in Platon. This tradition comes to the modern days and presents itself, as one of its requisites, the valorization of a subject of the knowledge, that contains an incorporeal and distant look, that turns out to develop a tirany of power. In the armandiano point of view, there is supposedly an adhesion to the visual strategies in order to, from them, develop an alternative potential to the use of images.That is what happens to the western view theme: the writer will take over this thematic to build a touchable look, infected ? as mixing elements of natural and artificial order ? and violent, that opposes a controlling, pacifier and distant look of an omnipresent and massive culture of the visual. The supposed naturality of the city of Rio de Janeiro, which geographical cultural marks are so intensely identifiable in its poetics, its vision already worldwide know as a postcard, the poet eliminated the common place cliche, that as he looks to it, indicates beautiful and conforting crystalized vision, the inability of its apprehensibility the violence of subjectivity.